1982
DOI: 10.1063/1.443817
|View full text |Cite
|
Sign up to set email alerts
|

Electronic polarizabilities of Tl+, Ag+, and Zn2+ ions estimated from refractive index measurements of TlNO3, AgNO3, and ZnCl2 melts

Abstract: Refractive indices of TlNO3, AgNO3, and ZnCl2 ionic melts were measured by a goniometer method using visible light at nine wavelengths. The refractive indices of these pure melts were represented conveniently as functions of both temperature and wavelength by means of a two-dimensional least squares method. According to the obtained formulas, the refractive indices were extrapolated to infinite wavelength so that the electronic polarizabilities of Tl+, Ag+, and Zn2+ ions in each pure melt were evaluated in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…While Heydweiller conducted some preliminary studies on the effect of temperature on salt polarizabilities, we perform a more systematic examination at six different temperatures from 25 to 65 °C. Iwadate et al found that the polarizabilities of ions in univalent molten salts are proportional to the cube of the bare ionic radius ( r bare 3 ), which is in accord with theoretical predictions of Machmer . However, for multivalent ions, theoretical data by Pauling and Tessman et al showed that this correlation does not hold.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…While Heydweiller conducted some preliminary studies on the effect of temperature on salt polarizabilities, we perform a more systematic examination at six different temperatures from 25 to 65 °C. Iwadate et al found that the polarizabilities of ions in univalent molten salts are proportional to the cube of the bare ionic radius ( r bare 3 ), which is in accord with theoretical predictions of Machmer . However, for multivalent ions, theoretical data by Pauling and Tessman et al showed that this correlation does not hold.…”
Section: Introductionmentioning
confidence: 74%
“…One of the key results in that work is the prediction of the slope of the refractive index with respect to salt concentration at low concentrations, in terms of the polarizability of the ionic species and the infinite dilution value of the partial molar volume of the salt, which is determined by extrapolation of the solution volume to zero salt concentration by including the Debye–Hückel correction. , Our predicted slopes for several different salts and different compositions of the water–acetonitrile liquid mixtures are in excellent agreement with experimental data. Since both the refractive index and the volume data can be easily and accurately measured with modern instrumentation, , which allows easy and accurate determination of the limiting slope, we can use the theory in reverse to obtain the polarizability of the salts from measured values of the limiting slope. In the current work, we employ this strategy to obtain the polarizabilities of 32 strong electrolyte salts in aqueous solution and compare our results with earlier results obtained through other methods.…”
Section: Introductionmentioning
confidence: 99%
“….Ag distances. To some extent this will reflect the relatively high polarisability of the Ag + cation [45], which translates to a "fluffiness" of its valence electron cloud. This "fluffiness" may well contribute to the superionic behaviour of some Ag + salts [46], where cation polarisability can play a key role in diffusion mechanisms [47].…”
Section: Bondingmentioning
confidence: 99%
“…It is, therefore, necessary to have an electric furnace with large heat capacity and good thermal uniformity. The goniometry can measure the refractive index with almost the same accuracy from room temperature to high temperature (1273 K). The other methods are somewhat inferior in terms of measurement accuracy.…”
Section: Introductionmentioning
confidence: 99%